2017
DOI: 10.1038/s41598-017-13563-1
|View full text |Cite
|
Sign up to set email alerts
|

The thermogenic actions of natriuretic peptide in brown adipocytes: The direct measurement of the intracellular temperature using a fluorescent thermoprobe

Abstract: In addition to the various effects of natriuretic peptides (NPs) on cardiovascular systems, increasing attention is being paid to the possibility that NPs induce adipose tissue browning and activate thermogenic program. We herein established a direct intracellular temperature measurement system using a fluorescent thermoprobe and investigated the thermogenic effects of A-type NP (ANP) on brown adipocytes. The thermoprobe was successfully introduced into rat brown adipocytes, and the temperature dependent chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 41 publications
2
66
1
2
Order By: Relevance
“…Recent evidence indicates that NP/cGMP-dependent protein kinase cascades also regulate the energy balance and glucose homeostasis 12 . We also demonstrated the thermogenic actions of NP in rat brown adipocytes through the p38 mitogen-activated protein kinase (MAPK)-uncoupling protein 1 (UCP1) pathway by increasing the intracellular temperature 13 . These findings suggested that NPs have a novel self-protective function when the core body temperature or the local tissue (including the heart itself) temperature decreases to a level that results in severe hemodynamic conditions, such as serious heart failure.…”
Section: Introductionmentioning
confidence: 91%
“…Recent evidence indicates that NP/cGMP-dependent protein kinase cascades also regulate the energy balance and glucose homeostasis 12 . We also demonstrated the thermogenic actions of NP in rat brown adipocytes through the p38 mitogen-activated protein kinase (MAPK)-uncoupling protein 1 (UCP1) pathway by increasing the intracellular temperature 13 . These findings suggested that NPs have a novel self-protective function when the core body temperature or the local tissue (including the heart itself) temperature decreases to a level that results in severe hemodynamic conditions, such as serious heart failure.…”
Section: Introductionmentioning
confidence: 91%
“…However, identification of NP receptors (NPRs) expression in adipose tissue shed new light on ANP/BNP pathways’ role in the whole-body homeostasis. Subsequently, ANP was found to induce lipolysis in white adipocytes and thermogenesis in BAT, while both NPs, via the cGMP-PKG-mTORC1 pathway, can increase UCP1 expression and mitochondrial content in adipocytes leasing to WAT browning [ 41 , 42 , 43 ]. Accordingly, mice with npra knockout suffer from cardiac hypertrophy and have significantly higher adipose tissue content than wild-type animals [ 41 ].…”
Section: Adipose Tissue Browningmentioning
confidence: 99%
“…Immunoblotting was performed as previously described [7,[26][27][28] with rabbit polyclonal anti-SGLT1 (1:200, #H-85; Santa Cruz Biotechnology, CA, USA), anti-GLUT4 (1:1000, #ab33780; Abcam, Cambridge, MA, USA), anti-GLUT1 (1:1000, #12939; Cell Signaling Technology, Tokyo, Japan), or mouse monoclonal anti-α1 Na-K-ATPase (1:1000, #ab7671; Abcam). The signals were detected using chemiluminescence.…”
Section: Immunoblottingmentioning
confidence: 99%
“…Total RNA was extracted from the frozen tissues using TRIzol reagent (Invitrogen) and a quantitative real-time PCR was performed using a StepOnePlus Real-time PCR System and the StepOne Software program (Applied Biosystems), as described previously [28]. The real-time PCR protocol consisted of one cycle at 95 °C for 20 s followed by 40 cycles at °C for 1 s and 60 °C for 20 s using the primers for Slc5a2 (Mm00453831_m1; Applied Biosystems) and GAPDH (Mn03302249_g1; Applied Biosystems).…”
Section: Rna Isolation Reverse Transcription (Rt) and Real-time Polymentioning
confidence: 99%